2020
DOI: 10.1016/j.clon.2019.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Application of Hereditary Renal Cell Carcinoma Risk Criteria to a Large Prospective Database

Abstract: Aims: To evaluate the clinical impact of the Canadian criteria for identifying patients and families at risk for hereditary renal cell carcinoma (RCC). Materials and methods: The Canadian hereditary RCC risk criteria were applied to patients from 16 centres in the Canadian Kidney Cancer information system (CKCis) prospective database. The primary end point was the proportion of patients who met at least one criterion. Results: Between January 2011 and May 2017, 8388 patients were entered in the database; 291 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…At present, histological and clinical features play an important role in the evaluation of genetic tests. A large prospective study applied to the Canadian Risk Criteria for Hereditary Renal Cell Carcinoma showed that 35% of patients met at least one genetic testing criterion, with non-clear cell histology criteria accounting for the largest proportion of patients, followed by age ≤45 years, first- or second-degree relative with any renal tumour and bilaterality or multifocality ( 30 ). However, previous studies demonstrated low referral of genetic testing in patients who met above-mentioned criteria.…”
Section: Discussionmentioning
confidence: 99%
“…At present, histological and clinical features play an important role in the evaluation of genetic tests. A large prospective study applied to the Canadian Risk Criteria for Hereditary Renal Cell Carcinoma showed that 35% of patients met at least one genetic testing criterion, with non-clear cell histology criteria accounting for the largest proportion of patients, followed by age ≤45 years, first- or second-degree relative with any renal tumour and bilaterality or multifocality ( 30 ). However, previous studies demonstrated low referral of genetic testing in patients who met above-mentioned criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Studies across numerous cancer types have begun to address this question, and mounting evidence demonstrates that testing guidelines miss an unacceptable number of individuals with PGVs in HCS genes across many cancer types (Fig 1B and Data Supplement). 1,2,21,29,50,[57][58][59][60][61][62][63][64][65][66][67][68][69] The percentage of patients with a PGV was substantial among those not meeting testing criteria (although usually lower compared with patients who met criteria). More importantly, because the absolute number of patients not meeting testing criteria is usually much greater than the number meeting criteria, the total number of patients with a PGV is also greater among those who do not meet criteria.…”
mentioning
confidence: 99%
“…10 A previous study assessing criteria for genetic screening in Canada identified PVs in 35% of patients with RCC who were referred for genetic testing; however, the available data did not allow for an investigation on the fraction of patients with PVs who did not meet referral criteria. 29 We realized that within the 56 Canadian patients with identified germline PVs in our study, only 15 (27%) meet the Canadian criteria for referral for genetic screening. Notably, most of those who are eligible are patients with nccRCC (Fig 4).…”
Section: Discussionmentioning
confidence: 75%